(untitled) (Perner’s Contacts, 2019)
At the time that vegins using the benefits of the fourth industrial revolution and automation, i tis not easy to keep the step on the labor market and i tis need to continuously adapt to a changing surrounding.It can be said, that the situation is more difficult in transport and logistics, that companies concern anotner current problems that are needed to expample: for high level of competition in the field of transport and logistics and least but not least problém is lack of labour. One of the most important elements in the company are its employees. The mos important employeees are in the field of transport and logistics when employees are the basic value of the service. Terefore in these papers I would like to focus on the current aspects of Industry 4.0 and their impact , in especially on the HR area in logistic companies.